PENGOLAHAN LIMBAH STIROFOAM MENJADI MODEL MOLEKUL 3D SEBAGAI BASIS PENGEMBANGAN EKONOMI KREATIF MASYARAKAT - Tamara Kartika; Fitriana Nur Hanifah; Hanifah Nur Widianingtyas; Indriana Kartini (EnviroUS, 2022)
Indonesia is the second largest contributor to plastic waste pollution in the world for the ocean, dominated by styrofoam. Hence, it is necessary to treat styrofoam waste. Meanwhile, there is a need for affordable plastic 3D molecular model kits. This study determines how to process styrofoam waste into a 3D molecular model kit, its effect on reducing environmental pollution, and its implementation in the home industry. Based on literature review, experiment, and market survey, styrofoam can be recycled using acetone into plastic as the kit material and has high market potential. A total of 37.5 kg of styrofoam is processed into 75 kits with an estimated five workers of unemployed and scavengers per production, BEP of 71 kits, and net profit is IDR 2,437,250.00 per month. Product sales will increase by 10% per year. This business is feasible with an NPV of IDR 956,299.30 and an IRR of 13.03%.